A Pragmatic Analysis On Commisive Utterances Used In "Rage Of Angels" Novel By Sidney Sheldon - Nugraheni., Hening Setya; , Dra. Siti Zuhriah Ariatmi, M.Hum; , Siti Fatimah, S. Pd, M. Hum (2014)
This study focuses on analyzing the type of commisive utterance and describing the violation of Grice Maxim's Cooperative Principle in commisive utterance in Rage of Angels novel. This study aim at 1) clarifying pragma linguistic form found in the utterance of commisive utterances in Rage of Angels, 2) describing the implicature of commisive utterance found in Rage of Angels, 3) describing the violation of Grice Maxim's Cooperative Principle in commisive utterances in Rage of Angels novel. It is conducted in order to know what maxims which are violated by the characters of Rage of Angels novel and the implicature of speaker's utterance when violating the maxims. The type of this research is descriptive qualitative, the several steps are done to analyze the data. In analyzing the type of commisive utterance the steps are: describing the data in the form of dialogue, describing the dialogue what is belongs into commisive utterance. In analyzing the implicature the steps are: describing the data in the form of dialogue and describing the intended meaning of speaker utterance and combines by describing pragma linguistic form: downgraders and upgraders. The study shows that 1) there are found 3 pragma linguistic forms, namely downgraders, upgraders, and the other has no pragma linguistic form 2) the implicature of speaker's utterances are to threats someone, convincing someone, to offering something, to promise, and to intends other to be careful. 3) the maxim which often violated by the characters is maxim of Quality, as many as 21 data, Maxim Quantity is violated as many as 14 data, Maxim of Relation is violated as many as 8 data and Maxim of Manner is violated as many as 8 data.